Cut to the chase: a review of CD26/dipeptidyl peptidase-4's (DPP4) entanglement in the immune system - Klemann, Christian; Wagner, L.; Stephan, M.; von Hörsten, Stephan (Clinical and Experimental Immunology, 2016)
CD26/DPP4 (dipeptidyl peptidase 4/DP4/DPPIV) is a surface T cell activation antigen and has been shown to have DPP4 enzymatic activity, cleaving-off amino-terminal dipeptides with either L-proline or L-alanine at the penultimate position. It plays a major role in glucose metabolism by N-terminal truncation and inactivation of the incretins glucagon-like peptide-1 (GLP) and gastric inhibitory protein (GIP). In 2006, DPP4 inhibitors have been introduced to clinics and have been demonstrated to efficiently enhance the endogenous insulin secretion via prolongation of the half-life of GLP-1 and GIP in patients. However, a large number of studies demonstrate clearly that CD26/DPP4 also plays an integral role in the immune system, particularly in T cell activation. Therefore, inhibition of DPP4 might represent a double-edged sword. Apart from the metabolic benefit, the associated immunological effects of long term DPP4 inhibition on regulatory processes such as T cell homeostasis, maturation and activation are not understood fully at this stage. The current data point to an important role for CD26/DPP4 in maintaining lymphocyte composition and function, T cell activation and co-stimulation, memory T cell generation and thymic emigration patterns during immune-senescence. In rodents, critical immune changes occur at baseline levels as well as after in-vitro and in-vivo challenge. In patients receiving DPP4 inhibitors, evidence of immunological side effects also became apparent. The scope of this review is to recapitulate the role of CD26/DPP4 in the immune system regarding its pharmacological inhibition and T cell-dependent immune regulation.
EVALuna2:24976